Essentials of gastroenterology - Friedman, Lawrence S.; Sitaraman, Shanthi V. (Wiley-Blackwell, 2012)
Highly practical and concise, this hands-on guide focuses on specific common clinical scenarios. Each section covers a particular area of the GI tract and follows a regular structure of: overview of normal function, physiology, pathophysiology, clinical presentation, differential diagnosis, diagnostic tests, and treatment